2018
DOI: 10.1371/journal.pone.0197552
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with advance directives completion among patients with advance care planning communication in Taipei, Taiwan

Abstract: BackgroundAlthough advance directives (AD) have been implemented for years in western countries, the concept of AD is not promoted extensively in eastern countries. In this study we evaluate a program to systematically conduct advance care planning (ACP) communication for hospitalized patients in Taiwan and identify the factors associated with AD completion.MethodsIn this retrospective evaluation of a clinical ACP program, we identified adult patients with chronic life-limiting illness admitted to Taipei City … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 24 publications
2
46
1
Order By: Relevance
“…10 In addition, a Patient Right to Autonomy Act was passed in 2015 and came into force on 6 January 2019; already annually over a thousand patients have participated in an advance care planning communication program undertaken since 2015 in Taipei. 11…”
Section: Introductionmentioning
confidence: 99%
“…10 In addition, a Patient Right to Autonomy Act was passed in 2015 and came into force on 6 January 2019; already annually over a thousand patients have participated in an advance care planning communication program undertaken since 2015 in Taipei. 11…”
Section: Introductionmentioning
confidence: 99%
“…Patient involvement ought to be higher in the societies where advance care planning and/or advance directive are mandatory in a certain situation (e.g. USA [20] and Taiwan [21,22]). Third, cultural perspectives and patients' (and family's) preferences that stem from them can be in uential.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Chu et al demonstrated that the implementation of palliative care training for healthcare providers and a program to routinely implement ACP for hospitalized patients with chronic life-limiting illness is feasible and successful in Taipei. [21] Providing physicians with appropriate educational opportunities and training, such as end-of-life care, psychological support for patients and their families, and communication skills training is essential.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Singapore passed the Advance Medical Directive Act in 1996 (Tee, Seet, Tan, & Choo, ) but in Hong Kong, advance directives are not yet supported with legislation (Chung et al, ). Taiwan was the first country in Southeast Asia to enact a Patient Self‐Determination Act in 2015 (Chu et al, ) similar to that which exists in the United‐States. This act is not specific to mental health but allows individuals with mental capacity to register an advance directive documenting their wishes for medical care (Chu et al, ).…”
Section: Legislationmentioning
confidence: 99%
“…Taiwan was the first country in Southeast Asia to enact a Patient Self‐Determination Act in 2015 (Chu et al, ) similar to that which exists in the United‐States. This act is not specific to mental health but allows individuals with mental capacity to register an advance directive documenting their wishes for medical care (Chu et al, ). Unsurprisingly, systematic reviews of the effectiveness of advance medical directives in Asia are lacking, possibly because the service user demand for such services has been low due to limited awareness (Chu et al, ; Gowda et al, ; Lai, Mohd Mudri, Chinna, & Othman, ; Tay, Chia, & Sng, ).…”
Section: Legislationmentioning
confidence: 99%